Contributions of joint torques, motion-dependent term and gravity to the generation of baseball bat head speed - Koike, S.; Mimura, K. (Procedia Engineering, 2016)
This study quantifies the dynamic contributions of joint torques, motion-dependent term, and gravity to the generation of baseball bat head speed. Baseball batting is considered one of the most difficult tasks in sports motions. The batter is required to increase the bat head speed within a short time and move the bat into the hitting point with proper timing. Based on multi-body dynamics, a high speed swing motion is caused by not only joint torques and gravity but also motion-dependent term (MDT). The MDT consisting of centrifugal force, Coriolis force and gyro moment shows the dynamic characteristics of multi-segment motion. Five collegiate baseball players participated in this experiment. They performed hitting a teed ball as strong as possible. The whole-body segments with bat were modelled as a system of sixteen-rigid linked segments, and anatomical constraint axes of the elbow, wrist, knee and ankle joints were modelled with geometrical constraint equations in order to consider the degree of freedom (DOF) of the joint. The equation of motion for the whole-body and bat was obtained by considering modelling errors, such as residual joint force and moment, and fluctuations in segment? lengths and joint constraint axes. Kinetic data of each hand and each foot were obtained by using an instrumented bat equipped with 28 strain gauges and 3 force platforms, respectively. The dynamic contributions of the joint moments, the motion-dependent term and the gravity term to the bat head speed were derived from the time integration of the equation of motion for the system. The results show that motion-dependent term is the largest contributor to the bat head speed in the last quarter of the forward swing phase. The contributions of the gravity and modelling error terms show small values. Motion dependent term is main generating factor to the head speed at the ball impact in baseball batting motion.